Project-Based Learning Strategies in Moral Beliefs: Building Character Through Real Activities - Fadl Lillah; Marno Nurullah; Samsul Susilawati (Journal Neosantara Hybrid Learning, 2024)
Moral beliefs play an important role in character education, especially in the modern era which is full of moral challenges. This study aims to explore the relevance of project-based learning strategies in strengthening the values of moral beliefs among students. The methodology used in this study includes a qualitative approach with data collection techniques through observation, interviews, and questionnaires. The main findings show that the application of project-based learning not only improves students’ understanding of moral beliefs, but also contributes to the development of positive character. The implications of this study show the need for the integration of innovative learning methods in the educational curriculum to form a generation with noble character.